'Though the treasure of nature's germens tumble all together': the EPO and patents on native traits or the bewitching powers of ideologies. (1st March 2015) - Girard, Fabien
Abstract : The growing criticism of patentability of native traits and genes (of plants obtained by traditional cross-breeding methods of species with the use of molecular biology methods) prompts questions about the constant erosion of boundaries in the field of non-patentability, which has been denounced by authoritative legal writers. But the issue currently at stake is even more worrisome, insofar as these new patents, the volume of which is constantly increasing, are blocking patents and cannot be expected to be circumvented by resort to cross-licensing agreements. Relying on the position expressly adopted by the European Patent Office (EPO) president in the Tomato II case, this paper brings to light the pro-patent bias that affects the functioning of the European patent system. It shows that this troubling phenomenon is rooted in governance issues. Above all, it stresses a deeper factor, namely the dual ideology of an exchange society and of science and technology (the logic of progress) that has dramatically severed the ties between the EPO and people's representative bodies, multi-stakeholder bodies and citizens themselves.